Beta-globin locus activation regions: conservation of organization, structure, and function. - Li, Q L (1990)
The human beta-globin locus activation region (LAR) comprises four erythroid-specific DNase I hypersensitive sites (I-IV) thought to be largely responsible for activating the beta-globin domain and facilitating high-level erythroid-specific globin gene expression. We identified the goat beta-globin LAR, determined 10.2 kilobases of its sequence, and demonstrated its function in transgenic mice. The human and goat LARs share 6.5 kilobases of homologous sequences that are as highly conserved as the epsilon-globin gene promoters. Furthermore, the overall spatial organization of the two LARs has been conserved. These results suggest that the functionally relevant regions of the LAR are large and that in addition to their primary structure, the spatial relationship of the conserved elements is important for LAR function.